Pendeteksi Harmonisa Arus pada sistem tenaga listrik dengan metode FFT (Fast Fourier Transform) berbasis LAB VIEW. - Rini Widayanti (FTE 14 UMY 017, 2014)
The fault of transmission electrical power causes the production, communication equipment, control equipment, personal computer work not optimum. This research implemented the fast Fourier Transform Theorem to hardware and software for harmonics detection on power system. Harmonics is a distortion in power system as effect from non linier load, harmonics will increase loses in transformation and motor, also make dysfunction from electric equipment like relay switching process. This system can process signal from times domain to frequency domain and shown it in graphic as real time in Personal Computer. Input signal from current sensor, increase with adder circuit and Analog to Digital Converter as signal sampling and convert analog signal into digital signal with digital data. This system has tested with Motor Generator and panel Control. Testing this system indicated there are harmonic around frequency 150 Hz and 300 Hz. Key Word: Harmonisa, Fast Fourier Transform, Data Aquisition